2016
DOI: 10.29252/ijrm.14.6.411
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical performance of antigen basedenzyme immunoassay (EIA) and major outer membrane protein (MOMP)-PCR for detection of genital Chlamydia trachomatis infection

Abstract: Background: Chlamydia trachomatis is the most common sexually transmitted bacterial pathogen worldwide. Early detection and treatment of C.trachomatis genital infection prevent serious reproductive complications. Objective:Performances of enzyme immunoassay (EIA) and major outer membrane protein (MOMP)-polymerase chain reaction (PCR) for diagnosis of genital C.trachomatis infection in women were compared.Materials and Methods:In this cross sectional study a total of 518 women volunteers were included (33.67±8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(28 reference statements)
2
2
0
Order By: Relevance
“…However, due to disappointing low sensitivity it cannot be recommended for the diagnosis of an acute chlamydial infection. Our findings are in accordance with findings from other studies where low sensitivity (20-60%) of rapid tests was observed [18][19][20][21][22]. Moreover, the study of Nateghi Rostami et al suggest primary screening of chlamydial infection in women by the low-cost EIA, but confirmation of the negative results by a DNA amplification method is required because of low sensitivity of EIA assays [23].…”
Section: Discussionsupporting
confidence: 92%
“…However, due to disappointing low sensitivity it cannot be recommended for the diagnosis of an acute chlamydial infection. Our findings are in accordance with findings from other studies where low sensitivity (20-60%) of rapid tests was observed [18][19][20][21][22]. Moreover, the study of Nateghi Rostami et al suggest primary screening of chlamydial infection in women by the low-cost EIA, but confirmation of the negative results by a DNA amplification method is required because of low sensitivity of EIA assays [23].…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study we found that antigen based enzyme immunoassay for C. trachomatis has 59.5% sensitivity [21]. In the present study, prevalence rate of C. trachomatis was 11.67% by PCR, while ienzume immunoassay demonstrates prevalence rate of 7.14% in women of the same region [21].…”
Section: Discussionsupporting
confidence: 49%
“…For molecular identification of C. trachomatis in genital specimens, ompI target gene encoding for chlamydial major outer membrane protein (MOMP) was amplified by nested PCR as previously described [21]. The sequence of external primers (Ex-p1/Ex-p2) and nested primers (In-p1/In-p2) are shown in Table 1 (CinnaGene, Tehran, Iran).…”
Section: Detection Of C Trachomatis Infectionmentioning
confidence: 99%
“…It also plays a role in pathogenesis and possibly adhesion. The MOMP along with the lipopolysaccharide, makes up the surface of the elementary body cell (Collar et al 2022;Rostami et al 2016).…”
Section: Discussionmentioning
confidence: 99%